Aggregate-Iterative Methods for the Approximation of Solutions of Boundary-Value Problems - Kostyshyn, L. P.; Shuvar, B. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We construct a special aggregate-iterative algorithm (a two-parameter method) for the iterative integration of a differential equation with two-point boundary conditions. We establish conditions for the convergence of this method and present partial cases of the two-parameter aggregate-iterative algorithm.